2020
DOI: 10.1155/2020/8739864
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Health of Akamkpa Forest Reserves in Southeastern Part of Nigeria Using Remote Sensing Techniques

Abstract: Assessment of forest health is very vital because forests form the largest terrestrial ecosystems on earth. The greenness of vegetation is one of the essential factors used in evaluating the health of forest reserves. This study is aimed at assessing the health of fifteen forest reserves in Southeastern part of Nigeria using meteorological data and MOD13A1-derived Normalized Difference Vegetation Index (NDVI) and Enhanced Vegetation Index (EVI). Related portions of the monthly MOD13A1 data, derived for the yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
(54 reference statements)
0
3
0
Order By: Relevance
“…NDVI and precipitation over cropland and mixed deciduous forest were strongly positively related, but no correlation was evident for dry evergreen forest. However, increased precipitation does not always correlate with vegetation indices; Ebinne et al (2020) reported a negative correlation between monthly precipitation and NDVI. Temperature has also been shown to have a strong negative correlation with NDVI (Wang et al 2003;Pei et al 2019); warmer temperatures cause more evapotranspiration, which limit plants growth.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…NDVI and precipitation over cropland and mixed deciduous forest were strongly positively related, but no correlation was evident for dry evergreen forest. However, increased precipitation does not always correlate with vegetation indices; Ebinne et al (2020) reported a negative correlation between monthly precipitation and NDVI. Temperature has also been shown to have a strong negative correlation with NDVI (Wang et al 2003;Pei et al 2019); warmer temperatures cause more evapotranspiration, which limit plants growth.…”
Section: Discussionmentioning
confidence: 99%
“…With the continued development of imaging sensors, this technique has become a useful and practical tool for characterizing forest health in a variety of ways and with high accuracy. With the availability of remote sensing data from satellite sensors such as moderate resolution imaging spectroradiometer (MODIS), advanced very high-resolution radiometer (AVHRR), Landsat, Sentinel, among others, the technology is even more useful for developing vegetation indices such as the normalized difference vegetation index (NDVI) and enhanced vegetation index (EVI), especially in broadleaf forests (Heumann et al 2007(Heumann et al , 2013Anees et al 2013;Zhang et al 2017;Barka et al 2019;Ebinne et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…[Source: Compiled from Kamran and Khorrami, 2022;Roshani et al, 2022;Kumari and Asok, 2017;Mahato et al, 2020;Mitra et al, 2021;Ebinne et al, 2020;Ishtiaque et al, 2016;Meng et al, 2016;Mandal et al, 2022. ]…”
Section: Gemi (Global Environment Monitoring Index)mentioning
confidence: 99%